Pengaruh Penyuluhan Terhadap Peningkatan Motivasi dan Tindakan dalam Mencuci Tangan dan Membuang Sampah Pada Anak Penyandang Tunagrahita di Sleman - Mohammad Mirza Fauzie; Lucky Herawati (Poltekkes Kemenkes Yogyakarta, 2014)
Clean and healthy behaviors such as hand washing with soap and waste disposing in proper place can be one of the ways to increase public health level. These activities should be done by everyone including those with mental retardation. This research was aimed to know the appro-priate health education method for improving motivation and action of those hand washing and waste disposing behavior among mental retarded children by conducting a quasi experiment with pre-test and post-test control group design. In the treatment group 1, the form of the experiment was health education with talk and followed by practical method, meanwhile in the treatment group 2, it was consisted of talk followed by video playing method; and in the control group, only talk method was carried out. The research subject was 45 mental retarded students of Panti Asih Special School in Pakem and Rela Bhakti I Special School in Gamping, Sleman, who were dis-tributed randomly into the research groups. Study results in the form of different scores data of motivation and action in hand washing and waste disposing were analysed with Kruskal-Wallis test at 95 % confidence level, and showed that significant differences in motivation of hand wa-shing (p- value 0,025) and waste disposing in proper place (p-value 0,004) were found between the treatments and control groups, especially in the cluster of above 13 years old. Significant dif-ference was also found in the action of hand washing (p-value 0.049) between the treatments and control groups; however, for waste disposing action, it was not significant enough (p-value 0,253). It can be concluded that the most appropriate methods are talk and practice method for increasing the motivation, and talk and video playing method for increasing the action, with put emphasis or give more attention on waste disposing matters.